DISARMING THE VALUE KILLERS: CSR VIEWED THROUGH A SHARP RISK MANAGEMENT LENS - Lahrech, Houssam (2011)
Why should rational, profit maximizing managers invest in managing CSR related risks? In this study, I propose a comprehensive framework for viewing CSR through a new risk management lens; a lens which would allow both managers and mainstream investors to reconsider the endless debate of the impact of CSR on the financial performance of the firm from another perspective. The main objective of this paper is to provide an insight on the shift in the risk management mindset with the recent development in Enterprise Risk Management (ERM). This relatively new notion provides a stronger ground for integrating CSR issues at the heart of the business risk model since it consider risks from a broader perspective. A perspective which allows for consideration for all types of risks including emerging CSR related risks. With ERM at the central stage, I develop a theoretical framework which would allow CSR and risks to converge. This framework is composed of 4 distinct constructs: Stakeholders‘ vulnerability assessment, corporate governance, communication, and financial performance.